HRPT2 mutations are associated with malignancy in sporadic parathyroid tumours. Issue 9 (5th September 2003) - Howell, V M; Haven, C J; Kahnoski, K; Khoo, S K; Petillo, D; Chen, J; Fleuren, G J; Robinson, B G; Delbridge, L W; Philips, J; Nelson, A E; Krause, U; et al.
Abstract : Background: Hyperparathyroidism is a common endocrinopathy characterised by the formation of parathyroid tumours. In this study, we determine the role of the recently identified gene, HRPT2, in parathyroid tumorigenesis. Methods: Mutation analysis of HRPT2 was undertaken in 60 parathyroid tumours: five HPT-JT, three FIHP, three MEN 1, one MEN 2A, 25 sporadic adenomas, 17 hyperplastic glands, two lithium associated tumours, and four sporadic carcinomas. Loss of heterozygosity at 1q24-32 was performed on a subset of these tumours. Results: HRPT2 somatic mutations were detected in four of four sporadic parathyroid carcinoma samples, and germline mutations were found in five of five HPT-JT parathyroid tumours (two families) and two parathyroid tumours from one FIHP family. One HPT-JT tumour with germline mutation also harboured a somatic mutation. In total, seven novel and one previously reported mutation were identified. "Two-hits" (double mutations or one mutation and loss of heterozygosity at 1q24-32) affecting HRPT2 were found in two sporadic carcinomas, two HPT-JT-related and two FIHP related tumours. Conclusions: The results in this study support the role of HRPT2 as a tumour suppressor gene in sporadic parathyroid carcinoma, and provide further evidence for HRPT2 as the causative gene in HPT-JT, and a subset of FIHP. In light of the strong association between mutations of HRPT2 and sporadic parathyroid carcinoma demonstrated in this study, it is hypothesised that HRPT2 mutation is an early event that may lead to parathyroid malignancy and suggest intragenic mutation of HRPT2 as a marker of malignant potential in both familial and sporadic parathyroid tumours.